Intracoronary administration of anisodamine and nicorandil in individuals undergoing primary percutaneous coronary intervention for acute inferior myocardial infarction: A randomized factorial trial - CHEN, CHUNHONG (Exp Ther Med, 2015)
In acute inferior myocardial infarction (AIMI), numerous conventional drugs that are used to improve the myocardial microcirculation can significantly reduce blood pressure (BP) and coronary perfusion pressure, aggravate bradyarrhythmia and cause a deterioration in the hemodynamic state of the whole body, which greatly limits the application of these drugs in clinical settings. The aim of the present study was to assess the effect of anisodamine and nicorandil regimens on the prevention of no-reflow (NR) and the amelioration of myocardial reperfusion in patients with AIMI undergoing primary percutaneous coronary intervention (PCI). A total of 104 consecutive patients with AIMI were included in this study and randomly assigned to one of four groups: A (control group), B (anisodamine group), C (nicorandil group) and D (anisodamine and nicorandil group). Patients underwent PCI via transradial artery access and the angiographic results were evaluated. Coronary diastolic BP (DBP) and systolic and mean BPs were measured by invasive catheterization. The primary end-point was a post-PCI Thrombolysis In Myocardial Infarction (TIMI) myocardial perfusion grade (TMPG) of 3. Composite end-points (mortality + new MI + target vessel revascularization) were evaluated during the hospital stay and 30 days after discharge. Following the procedure, the proportion of patients achieving TMPG 3 was significantly higher in group D than that in the other groups (P=0.014); furthermore, the incidence of a postprocedural TIMI score of 3 was the highest in group D. Three days after the procedure, the peak creatine kinase-MB and cardiac troponin I levels were the lowest and the left ventricular ejection fraction was the highest in group D. A thrombus score of 3/4 and low DBP were the independent risk factors for poor myocardial reperfusion (expressed as TMPG <3), while 2 mg anisodamine plus 2 mg nicorandil prior to PCI was protective for optimal myocardial reperfusion following the procedure. The combination of anisodamine and nicorandil can effectively ameliorate myocardial reperfusion and protect cardiac function in patients with AIMI undergoing primary PCI.